Accumulation of Microplastics and Potentially Toxic Elements in Plant Leaves Along an Urbanization Gradient in Bangladesh - Md. Sohel Parvez; Herta Czédli; Md. Imdadul Hoque; Mohammad Mizanur Rahman; Armin Anwar; Abu Hena Mohammad Mezbah Uddin; Md. Siddiq Hasan; Dina Bibi; Béla Tóthmérész; Tibor Magura; Edina Simon (Toxics)
Potentially toxic elements (PTEs) and microplastics (MPs) in the atmosphere raise widespread apprehension due to their association with the ecosystem and public health. The accumulation of airborne MPs and PTEs was analyzed in Polyalthia longifolia leaves, and the Pollution Index (PI) was calculated along an industrial, residential, and rural gradient in Bangladesh. Only polyethylene terephthalate (PET) was found in the highest concentration in industrial areas compared to other areas. In leaves, a significantly higher Cd, Pb, and Zn concentration was found in industrial regions compared to residential and rural areas. For Cd, the PI was observed to be higher than 1 in rural areas, indicating a moderate level of pollution; it was higher than 3 in residential areas, showing considerable pollution; and it was found to be more than 6 in industrial areas. The higher concentration of both MPs and PTEs with increasing urbanization reflects the influence of anthropogenic activities. The findings of the study demonstrate the fascinating potential of P. longifolia tree leaves as a promising bioindicator for air quality biomonitoring.